2016
DOI: 10.1071/rd14237
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins 7 and 11 in boar spermatozoa: detection, localisation and relationship with sperm quality

Abstract: Aquaporins (AQPs) are integral membrane water channels that allow transport of water and small solutes across cell membranes. Although water permeability is known to play a critical role in mammalian cells, including spermatozoa, little is known about their localisation in boar spermatozoa. Two aquaporins, AQP7 and AQP11, in boar spermatozoa were identified by western blotting and localised through immunocytochemistry analyses. Western blot results showed that boar spermatozoa expressed AQP7 (25kDa) and AQP11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 45 publications
1
37
1
1
Order By: Relevance
“…On the other hand, AQP7 staining has been reported to change in response to sperm cryopreservation in boars but not in bulls (Prieto‐Martínez, Morató et al., ; Prieto‐Martínez, Vilagran et al., ; Prieto‐Martínez et al., ). Indeed, while Prieto‐Martínez, Vilagran et al.…”
Section: Aquaporins In Mammalian Spermmentioning
confidence: 99%
“…On the other hand, AQP7 staining has been reported to change in response to sperm cryopreservation in boars but not in bulls (Prieto‐Martínez, Morató et al., ; Prieto‐Martínez, Vilagran et al., ; Prieto‐Martínez et al., ). Indeed, while Prieto‐Martínez, Vilagran et al.…”
Section: Aquaporins In Mammalian Spermmentioning
confidence: 99%
“…Recently, it has been reported the presence of integral membrane water channels, aquaporins 7 and 11 in boar sperm. The amount of aquaporin 11 shows a correlation with sperm motility and membrane integrity [7].…”
Section: Introductionmentioning
confidence: 99%
“…As well, AQP-7 has been found in human spermatozoa (Moretti et al 2011) and in the seminiferous epithelium, suggested as associated with volume regulation in germ cells ). AQP-7 has been immunocytochemically (ICC) detected in boar spermatozoa using different commercial antibodies (Prieto-Mart ınez et al 2014;Vicente-Carrillo 2015) and its role related to sperm quality (Prieto-Mart ınez et al 2014) and/or capacity to react under different osmotic pressures (Vicente-Carrillo 2015). The ICC of the above studies depicted different localization of AQP-7, perhaps due to differences in the specificity of the antibodies used, a matter for reported concern regarding AQPs (Yeung 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, this AQP-7 would also provide a port for glycerol as a carbon source for mature sperm metabolism. AQP-7 has been immunocytochemically (ICC) detected in boar spermatozoa using different commercial antibodies [17][18] and its role related to sperm quality 18 and/or capacity to react under different osmotic pressures 17 . The ICC of the above studies depicted different localization of AQP-7, perhaps due to differences in the specificity of the antibodies used, a matter for reported concern regarding AQPs…”
Section: Introductionmentioning
confidence: 99%